Microfinance: Does it hold its promises? A survey of recent literature - Aliya Khawari (Hamburg Institute of International Economics (HWWA), 2004)
Poverty alleviation has been the main target of developmental projects world-wide. However, only a few ideas have stirred so much attention in the last two decades as that of the provision of microfinance through specialised institutions. This paper provides a survey of the vast literature that has developed in this field. Though most of the evidence and literature on the subject appears self-praising, nonetheless there is much more to the concept than one can imagine. The establishment of microfinance institutions (MFIs) world-wide for the provision of collateral free loans to the poor through mechanisms and instruments not known to normal commercial banks has set new milestones in the field of financial services. With 900 million households in the less developed countries left without any access to formal financial services, this might just be the key to address market failures in the financial landscape.
Keywords: O16; O12; 330; Microfinance institutions; group lending; sustainability; target groups; Mikrofinanzierung; Wirtschaftspolitische Wirkungsanalyse; Armutspolitik; Entwicklungsländer